The Effect of the Separation of Ownership from Control on Accounting Policy Decisions. - Smith, E. Daniel (The Accounting Review, 1976)
Abstract This article cites a study which assesses the effect of the separation of ownership from control on accounting policy decisions. Many theories of management behavior in manager firms consistently argue that a gradually rising performance measure is in management's best interest. This study is an empirical investigation of the accounting policy decisions which were made by 110 firms during the 9-year period between 1954-1962. The firms considered for inclusion in this study were listed on the New York Stock Exchange in December 1954, as reported in the U.S. Senate Staff Report. Fifty-seven managers and fifty-three owner firms were selected randomly from this population for inclusion in this study. In this study, control refers to the power to direct the affairs of the corporation or to determine the broad policies guiding the corporation. Results of this study extend the research previously reported in the accounting literature by empirically drawing the distinction between owner-controlled firms and manager-controlled firms for the first time. Some of the results lend empirical evidence to the importance of distinguishing between owner and manager control.